Papers of Charles Bliss - Bliss, Charles K. (Charles Kasiel) (1943)
Correspondence, cuttings, research notes, and roneod material relating to Bliss'several publications on semantography and communications. The newspaper and journal cuttings were arranged under the headings Language, Education, Biology, History, Religion, and Pioneers of new ideas, and, together with work notes and early drafts of articles form the basis of his two most important books Semantography (Blissymbolics) and The Invention and Discovery that will change our lives. The Papers also contain over 200 issues of Bliss' roneoed newsletters Semantography Series (1949, 1-1964, no. 203). The correspondence, which is arranged alphabetically, reveals the world-wide interest shown in Bliss' work. Principal correspondents are Douglas Everingham, Professor Oliver Reiser, and Fritz Treuer.
Manuscript reference no. : MS 3884.
Guide to collections of manuscripts relating to Australia
Research chemist and inventor of a universal language employing symbols. Born of Jewish parents in Austria (1896); graduate in chemical engineering in 1922; escaped to England from German concentration camp, travelled through China, and settled in Australia in 1946.
Finding aid available online.
Keywords: Bliss, Charles K. -- Archives; Everingham, D. N. -- 1923- -- Correspondence; Reiser, Oliver L. -- 1895-1974 -- Correspondence; Treuer, Fritz -- Correspondence; Philosophers -- Australia -- Archives; Communication -- Graphic methods; Pasigraphy; Chemists; Philosophers